The Current Evidence for the Use of Safinamide for the Treatment of Parkinson’s Disease - Abbruzzese G; Barone P; Lopiano L; Stocchi F (Dove Medical Press, 2021)
Giovanni Abbruzzese,1 Paolo Barone,2 Leonardo Lopiano,3 Fabrizio Stocchi4 1Department of Neuroscience, University of Genova, Genova, Italy; 2School of Medicine, University of Salerno, Salerno, Italy; 3Department of Neuroscience, University of Turin, AOU Città della Salute e della Scienza, Torino, Italy; 4Department of Neurology, University and Institute for Research and Medical Care, San Raffaele Roma, Rome, ItalyCorrespondence: Fabrizio StocchiDepartment of Neurology, University and Institute for Research and Medical Care, San Raffaele Roma, Via della Pisana 235, Rome, 00163, ItalyTel +390653352311Fax +39066789158Email fabrizio.stocchi@fastwebnet.itIntroduction: Parkinson’s therapeutic interventions are only symptomatic. An optimal treatment should therefore address the largest number of motor and non-motor symptoms, to manage patients at best. Safinamide is one of the most recent approved drugs for fluctuating patients, in add-on to levodopa, that remains the gold standard treatment. It has a unique mechanism of action, both dopaminergic (as MAO-B inhibitor) and glutamatergic (through Na+ channel blockade). Results from Phase III trials, post-hoc analyses and real-life experiences suggest a beneficial effect on motor (such as tremor, bradykinesia, rigidity and gait) and non-motor (pain, mood, sleep) symptoms.Areas Covered: Here, the authors discuss clinical efficacy and safety of safinamide, identifying the patients’ profiles that could benefit most. A search in PubMed was performed in September 2020, with no time limits. Publications’ abstracts were reviewed.Conclusion: Safinamide is peculiar due to its double mechanism of action. Its benefits in improving motor functions and fluctuations, and some non-motor symptoms, could have a valuable impact on patients’ quality of life (QoL), together with its safety profile.Keywords: glutamate, motor fluctuations, Parkinson’s disease, safinamide